2014
DOI: 10.1007/s10461-014-0895-8
|View full text |Cite
|
Sign up to set email alerts
|

Men Who Have Sex with Men in Mozambique: Identifying a Hidden Population at High-risk for HIV

Abstract: The population of men who have sex with men (MSM) has been largely ignored in HIV-related policies and programming in Mozambique and there is little information about the contribution of MSM to the HIV epidemic. An integrated biological and behavioral study among MSM using respondent-driven sampling was conducted in 2011 in Maputo, Beira and Nampula/Nacala. Men who reported engaging in oral or anal sex with other men in the last 12 months answered a questionnaire and provided a blood sample for HIV testing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…12,19,23,24,49,6567 Sandfort et al 21 found that men in South Africa who tested HIV-positive in the study were more likely to be categorized as hazardous drinkers as measured by the AUDIT than HIV-negative men (54.5% versus 40.0%; AOR: 1.81; 95%CI: 1.06, 3.07). Baral et al 68 reported that men in Swaziland who drank alcohol at least one day in the preceding month were not more likely to be HIV infected than other men (AOR based on weighted data: 2.18; CI95%: 0.60, 7.95).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…12,19,23,24,49,6567 Sandfort et al 21 found that men in South Africa who tested HIV-positive in the study were more likely to be categorized as hazardous drinkers as measured by the AUDIT than HIV-negative men (54.5% versus 40.0%; AOR: 1.81; 95%CI: 1.06, 3.07). Baral et al 68 reported that men in Swaziland who drank alcohol at least one day in the preceding month were not more likely to be HIV infected than other men (AOR based on weighted data: 2.18; CI95%: 0.60, 7.95).…”
Section: Resultsmentioning
confidence: 91%
“…Based on the AUDIT, Sandfort et al 21 classified 44.4% of the men in a South African study as hazardous drinkers; Lane et al 24 reported that almost all of the MSM in South African rural areas in their study met AUDIT-C criteria for alcohol misuse; in Mozambique proportions of hazardous drinkers based on the AUDIT-C varied by town, ranging from 32.3% to 43.8%. 49 Among MSM in Kenya, Muraguri et al 32 estimated 22.7% of the men to be alcohol dependent. In his study among South African MSM, Lane et al 30 created three categories of men: irregular drinkers (men who drank alcohol less than once per week and were drunk less than once a week); regular drinkers (men who drank alcohol once a week or more and were drunk less than once a week); and regular drinkers to intoxication (men who drank alcohol once a week or more, and were drunk once a week or more), with 36.1%, 23.8%, and 40.1% of the men filling these categories, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has important implications; finding one person from a specific hard-to reach population could serve as a gateway to others from this same population. This phenomenon has been observed with frequency in sub-Saharan African high-risk populations, such as sex workers, injection drug users and men who have sex with men, [17][18][19][20][21][22][23] but this phenomenon is less well described among patients with STI who primarily experience risk from heterosexual sexual contact with the general population. [24][25][26][27] This observation is important since heterosexual transmission in the general population is the primary source of HIV transmission in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropological work has broadened understanding of the range of personal and family motives for sexual risk-taking and risk protection across economic classes (Groes-Green, 2009a, 2012, 2013. Authors have proposed how health and social marketing can improve to address HIV risk communication for Mozambicans, especially for community subgroups (Baltazar et al, 2015;Nalá et al, 2015), and have shed light on why some MSP communication fails to resonate with marginalised populations (GroesGreen, 2009a).…”
Section: Subsequent Researchmentioning
confidence: 99%